1999
DOI: 10.1590/s1415-47571999000300010
|View full text |Cite
|
Sign up to set email alerts
|

New cases of supernumerary chromosomes in characiform fishes

Abstract: Supernumerary chromosomes were described for five species of Neotropical characiform fishes. These extra chromosomes were small, acrocentric and fully heterochromatic in Leporinus friderici from two different localities as well as in Leporinus sp., but metacentric and fully heterochromatic in Cyphocharax modesta and Prochilodus nigricans. In Characidium cf. zebra, this element was small, acrocentric and euchromatic. GC-rich DNA blocks were observed in the supernumerary chromosome of Leporinus sp. using chromom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 15 publications
4
46
0
6
Order By: Relevance
“…Few investigators have reported on the base composition of supernumerary chromosomes in fish; however, results similar to those obtained here were published by Vênere et al (1999). These authors treated the chromosomes of Leporinus sp.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Few investigators have reported on the base composition of supernumerary chromosomes in fish; however, results similar to those obtained here were published by Vênere et al (1999). These authors treated the chromosomes of Leporinus sp.…”
Section: Discussionsupporting
confidence: 82%
“…NUP690, NUP1664, NUP1786, NUP1826 (NUP refers to the ichthyological collection of NUPELIA, Núcleo de Pesquisas em Limnologia, Ictiologia e Aquicultura of Universidade Estadual de Maringá, PR, Brazil) (Borin and Martins-Santos, 2004) and Megalonema platanum (Günther, 1880) (Carvalho, 2008). There are few papers that have examined the base pair composition of these chromosomes in fish (Vênere et al, 1999;Maistro et al, 2000Maistro et al, , 2002Jesus et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…and Siluriformes (n=21 spp.) (Fenocchio and Bertollo 1990, Dias and Foresti 1993, Venere et al 1999, Carvalho et al 2008. In these orders, the frequency of B chromosomes is the highest found in all fish orders to date, including the large order Perciformes.…”
Section: Bs and Sex Chromosomes Accumulation In Fish Genomesmentioning
confidence: 99%
“…However, Voltolin et al (2011) recently detected the presence of eight and nine supernumerary chromosomes in individuals of this species resulting from induced crossings. Supernumerary chromosomes exhibit a remarkable variation in size and morphology among fish, i.e., the occurrence of large genomic elements as macrochromosomes was described in species of the genus Astyanax (Maistro et al 1992, Salvador and Moreira-Filho 1992, Vicente et al 1996, Moreira-Filho et al 2001, Ferro et al 2003, Hashimoto et al 2008; of medium size in Rhamdia Bertollo 1990, Fenocchio et al 2000); and also as small elements identified as microchromosomes in Prochilodus (Pauls and Bertollo 1983, Venere et al 1999, Cavallaro et al 2000, Oliveira et al 2003, Voltolin et al 2009). Artoni et al (2006), studying specimens of P. lineatus from the Mogi-Guaçu River, observed the presence of three types of supernumerary microchromosomes in this species, which were classified as B-acrocentric, B-metacentric, and B-submetacentric.…”
Section: -1377mentioning
confidence: 99%